Aid to the enemy: linking development and peacebuilding on the Korean peninsula. Issue 4 (7th August 2016) - Kim, Dong Jin
Abstract: This article discusses the link between development and peacebuilding to analyze South Korean aid activities in North Korea in the context of the Korean conflict, where there are deep-rooted cycles of conflict episodes, and to explore the possibility of aid for peace on the Korean peninsula in the future. The Korean conflict is a large part of what makes South Korean aid to North Korea ineffective. For the past 20 years, South Korean aid to North Korea has fluctuated greatly, due to the context of the Korean conflict. The Korean conflict, once seemingly on the way to resolution, appears to have reverted to a time before the end of the Cold War. Many people in both the North and the South still see each other as the enemy. Most of the South Korean aid projects in North Korea have been suspended indefinitely and the fluctuation of aid to North Korea caused serious debates within South Korean society. At one point, the debates grew so heated that they were called the 'South–South conflict'. Building on the conceptual framework of conflict sensitive development and strategic peacebuilding, this article argues that, to overcome the current impasse, all stakeholders must better understand the context of the Korean conflict and the interaction between the context and themselves, and develop a comprehensive strategy together, to encompass the multiple issues raised by the Korean conflict, as strategic peacebuilding proposes.